Efektivitas Penanganan Dispensasi Kawin Pasca Berlakunya Undang-Undang Nomor 16 Tahun 2019 di Ponorogo - Nur Laela Kusna; Miftahul Huda; Iza Hanifuddin (Institut Agama Islam Negeri Ponorogo, 2023)
This research was motivated by the increasing number of requests for marriage dispensation atthe Ponorogo Religious Court after the enactment of Law no. 16 of 2019. This law is expectedto provide a major transformation in efforts to prevent early marriage with all its derivativesocial problems. This field research using a qualitative approach produced two conclusions,namely: (1) in terms of the factors causing the increase, Law Number 16 of 2019 has not beeneffective. The data that has been analyzed shows that apart from the same causal factors as thecausal factors before the existence of Law Number 16 of 2019, such as being pregnant out ofwedlock, having given birth to a child, parents are worried that their children will fall intothings that are prohibited by religion, low economic conditions, poor education. low, there is anew causal factor, namely public ignorance about the increase in the marriage age limit. If werefer to the definition made by Soejono Soekanto, the law is said to be effective if it is able toachieve its objectives and (2) Judges as law enforcers in handling marriage dispensation casesare guided by existing regulations and are deemed to have been effective in implementing LawNumber 16 of 2019 in the Religious Courts. The judge has taken action in the form of giving adecision based on the law and actual factual circumstances. Considerations in the determinationrefer to existing regulations, especially Law no. 16 of 2019.